Visualization and ligand-induced modulation of dopamine receptor dimerization at the single molecule level - Tabor, Alina; Weisenburger, S; Banerjee, Ashutosh; Purkayastha, Nirupam; Kaindl, Jonas; Hübner, Harald; Wei, Luxi; Groemer, Teja W.; Kornhuber, Johannes; Tschammer, Nuska; Birdsall, Nigel J.M.; Mashanov, Gregory I.; et al. (Scientific Reports, 2016)
G protein-coupled receptors (GPCRs), including dopamine receptors, represent a group of important pharmacological targets. An increased formation of dopamine receptor D-2 homodimers has been suggested to be associated with the pathophysiology of schizophrenia. Selective labeling and ligand-induced modulation of dimerization may therefore allow the investigation of the pathophysiological role of these dimers. Using TIRF microscopy at the single molecule level, transient formation of homodimers of dopamine receptors in the membrane of stably transfected CHO cells has been observed. The equilibrium between dimers and monomers was modulated by the binding of ligands; whereas antagonists showed a ratio that was identical to that of unliganded receptors, agonist-bound D-2 receptor-ligand complexes resulted in an increase in dimerization. Addition of bivalent D-2 receptor ligands also resulted in a large increase in D2 receptor dimers. A physical interaction between the protomers was confirmed using high resolution cryogenic localization microscopy, with ca. 9 nm between the centers of mass.